Long-term follow up of carbohydrate metabolism and adverse events after termination of Omnitrope® treatment in children born small for gestational age. (May 2021) - Walczak, Mieczyslaw; Szalecki, Mieczyslaw; Horneff, Gerd; Lebl, Jan; Kalina-Faska, Barbara; Giemza, Tomasz; Moldovanu, Florentina; Nanu, Michaela; Zouater, Hichem
Background: Recombinant human growth hormone (rhGH) therapy can affect carbohydrate metabolism and lead to impaired glucose tolerance during treatment. In addition, short children born small for gestational age (SGA) are predisposed to metabolic abnormalities. This study assessed the long-term safety of rhGH (Omnitrope®) use in short children born SGA. Methods: This was a follow-up observational study of patients from a phase IV study. The baseline visit was the final visit of the phase IV study. Further visits were planned after 6 months (F1), 1 year (F2), 5 years (F3), and 10 years (F4). The primary objective was to evaluate the long-term effect of rhGH treatment on the development of diabetes mellitus; secondary objectives included incidence/severity of adverse events (AEs). Results: In total, 130 subjects were enrolled in the follow-up study; 99 completed F1, 88 completed F2, and 13 completed F3 (no subject reached F4). The full analysis set for evaluation comprised 118 patients (64 female). Mean (standard deviation) duration of follow up was 39.6 (24.4) months. No subject was newly diagnosed with diabetes. The results for carbohydrate metabolism parameters were consistent with this finding. A total of 144 AEs were reported in 54 subjects; these were mostly of mild-to-moderate intensity (96.5%) and not suspected to be related to previous rhGH treatment (94.4%). Serious AEs ( n  = 18) were reported in eight patients; three (in one patient) were suspected as possibly related to previous rhGH treatment (anemia, menorrhagia, oligomenorrhoea). One fatal event occurred (sepsis), which was judged as not related to previous rhGH treatment. Conclusions: None of the participating subjects, who had all been previously treated with Omnitrope® in a phase IV study, developed diabetes during this follow-up study. In addition, no other unexpected or concerning safety signals were observed.